Bioencapsulation of Streptomyces sp. with Sodium Alginate for Control Fusarium sp. in Shallot Plants - Widyananda, Kanaya Syafina; Purnawati, Arika; Wiyatiningsih, Sri (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2025)
This study investigated the effects of Streptomyces sp. encapsulated in sodium alginate beads on the growth and health of shallot (Allium cepa L.) plants. Different sodium alginate concentrations (2%, 2.5%, and 3%) and application timings (7 days before transplanting and at transplanting) were tested. The mass and diameter of the beads showed slight decreases over storage time, indicating some shrinkage but maintaining structural integrity to protect the bacteria. Encapsulation efficiency was highest at 3% sodium alginate, which also correlated with increased bead stability. Viability tests revealed that Streptomyces maintained high colony-forming units (CFU) across the treatments, confirming the protective effect of the encapsulation. Application of beads significantly reduced Fusarium wilt disease intensity and improved bulb weight. Treatments with higher sodium alginate concentrations and earlier application times showed the most pronounced benefits. These findings demonstrate that beads using optimal sodium alginate concentration and timing enhance microbial viability and biological control efficacy, contributing to healthier and more productive shallot cultivation.